2022
DOI: 10.1007/s00259-022-05804-x
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the dopamine transporter imaging for the differential diagnosis of parkinsonism using deep learning

Abstract: Purpose This work attempts to decode the discriminative information in dopamine transporter (DAT) imaging using deep learning for the differential diagnosis of parkinsonism. Methods This study involved 1017 subjects who underwent DAT PET imaging ([11C]CFT) including 43 healthy subjects and 974 parkinsonian patients with idiopathic Parkinson’s disease (IPD), multiple system atrophy (MSA) or progressive supranuclear palsy (PSP). We developed a 3D deep convo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…In addition, artificial intelligence technology includes machine learning such as e classification and regression tree (CART), support vector machines (SVM) and random forest (RF) classifier, plays a certain role in assisting to determine the cutoff values and further diagnosing Parkinson’s syndrome by combing MIBG scintigraphy, and its effectiveness has been well demonstraed in previous studies( Nuvoli et al, 2017 , 2020 ; Iwabuchi et al, 2021 ). Besides, some studies have applied deep learning to DAT PET and FDG PET scans to analyze multiple regions as well as their correlation, which proved that it was helpful for the early diagnosis of Parkinson’s disease ( Wu et al, 2022 ; Zhao et al, 2022 ). In future studies, we can also refer to the above methods to simultaneously analyze MIBG uptake in sympathetic distributed organs including salivary glands and heart from SPECT/CT imaging, so as to improve the combined multiorgan MIBG imaging for the differential diagnosis of Parkinson’s disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, artificial intelligence technology includes machine learning such as e classification and regression tree (CART), support vector machines (SVM) and random forest (RF) classifier, plays a certain role in assisting to determine the cutoff values and further diagnosing Parkinson’s syndrome by combing MIBG scintigraphy, and its effectiveness has been well demonstraed in previous studies( Nuvoli et al, 2017 , 2020 ; Iwabuchi et al, 2021 ). Besides, some studies have applied deep learning to DAT PET and FDG PET scans to analyze multiple regions as well as their correlation, which proved that it was helpful for the early diagnosis of Parkinson’s disease ( Wu et al, 2022 ; Zhao et al, 2022 ). In future studies, we can also refer to the above methods to simultaneously analyze MIBG uptake in sympathetic distributed organs including salivary glands and heart from SPECT/CT imaging, so as to improve the combined multiorgan MIBG imaging for the differential diagnosis of Parkinson’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…a: the left parotid gland uptake ratio in early images; b: the left submandibular gland uptake ratio in early images; c: the right submandibular gland uptake ratio in early images; d: the left submandibular gland uptake ratio in delayed images; e: the heart uptake ratio in early images; f: the heart uptake ratio in delayed images. Frontiers in Aging 08 frontiersin.org of Parkinson's disease (Wu et al, 2022;Zhao et al, 2022). In future studies, we can also refer to the above methods to simultaneously analyze MIBG uptake in sympathetic distributed organs including salivary glands and heart from SPECT/CT imaging, so as to improve the combined multiorgan MIBG imaging for the differential diagnosis of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with DAT PET, Zhao et al, found differences in basal ganglia relative binding ratios among patients with different parkinsonisms but failed to demonstrate differences between PD and MSA (33). Despite the authors extracting conventional radiomics features which were significantly different among atypical parkinsonisms no predictive model was built for the differential diagnosis, because the study was centered on deep learning-based applications.…”
Section: Diagnosis and Early Differentiation From Atypical Parkinsonismsmentioning
confidence: 99%
“…Striatal uptake on dopamine transporter (DAT) scans is usually abnormal in parkinsonian disorders but does not typically differentiate between parkinsonian disorders. However, machine learning approaches using deep neural networks and regional values have shown that classification of PSP-RS from PD and MSA can be improved (sensitivity ¼ 82%, specificity ¼ 94%) [27,28]. Imaging also been used to investigate the cholinergic system in PSP.…”
Section: Investigating Subcortical Brain Systemsmentioning
confidence: 99%